Out of the Shadows The Health and Well-Being of Private Contractors Working in Conflict Environments - Dunigan, Molly (RAND Corporation, 2013)
Private contractors have been deployed extensively around the globe for the past decade and may be exposed to many of the stressors that are known to have physical and mental health implications for military personnel. Results from a RAND survey offer preliminary findings about the mental and physical health of contractors, their deployment experiences, and their access to and use of health care resources.